2015
DOI: 10.5751/ace-00772-100203
|View full text |Cite
|
Sign up to set email alerts
|

Sex ratios of Mountain Plovers from egg production to fledging

Abstract: ABSTRACT. Skewed sex ratios can have negative implications for population growth if they do not match a species' life history. A skewed tertiary sex ratio has been detected in a population of Mountain Plover (Charadrius montanus), a grassland shorebird experiencing population declines. To study the cause of the observed male skew, we examined three early life stages between egg and fledgling in eastern Colorado from 2010 to 2012. This allows us to distinguish between egg production and chick survival as an exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…For example, primary sex ratio can refer to the ratio at fertilization, (Aslam et al., ; DuRant et al., ; Eiby et al., ; Krackow, ), at laying (Alonso‐Alvarez, ; Czyż, Rowiński, & Wesołowski, ; Szász, Kiss, & Rosivall, ), or in the egg (Donald, ; Riordan, Lukacs, Huyvaert, & Dreitz, ). Secondary sex ratio can refer to the ratio after laying (DuRant et al., ; Szász et al., ), after hatching (Kilner, ; Riordan et al., ), at hatching (Eiby et al., ; Saunders & Cuthbert, ), at the chick stage (Czyż et al., ; Donald, ), or at fledging (Alonso‐Alvarez, ; Romano, Ambrosini, Caprioli, Bonisoli‐Alquati, & Saino, ), although there are distinct stages associated with the secondary sex ratio (i.e., embryo development, hatching, and fledging). To avoid semantic confusion on the difference of definition across studies, we need to define offspring sex ratio with respect to the major growth stages, which are at clutch, during incubation (embryo development), at hatching, and at fledging.…”
Section: Discussionmentioning
confidence: 99%
“…For example, primary sex ratio can refer to the ratio at fertilization, (Aslam et al., ; DuRant et al., ; Eiby et al., ; Krackow, ), at laying (Alonso‐Alvarez, ; Czyż, Rowiński, & Wesołowski, ; Szász, Kiss, & Rosivall, ), or in the egg (Donald, ; Riordan, Lukacs, Huyvaert, & Dreitz, ). Secondary sex ratio can refer to the ratio after laying (DuRant et al., ; Szász et al., ), after hatching (Kilner, ; Riordan et al., ), at hatching (Eiby et al., ; Saunders & Cuthbert, ), at the chick stage (Czyż et al., ; Donald, ), or at fledging (Alonso‐Alvarez, ; Romano, Ambrosini, Caprioli, Bonisoli‐Alquati, & Saino, ), although there are distinct stages associated with the secondary sex ratio (i.e., embryo development, hatching, and fledging). To avoid semantic confusion on the difference of definition across studies, we need to define offspring sex ratio with respect to the major growth stages, which are at clutch, during incubation (embryo development), at hatching, and at fledging.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, undetected individuals were assigned an unknown status. We included this unknown status as a third state in addition to live and dead and estimated survival using transition probabilities (Ψ) in a multistate model ( 37 ). We also estimated fledgling survival for gray-headed juncos using the multistate approach above but included treatment (control and enclosure), mass, and wing length as covariates to examine their influence on variation in fledgling survival.…”
Section: Methodsmentioning
confidence: 99%
“…Liker et al [44] found that species with male-biased care usually have male-biased adult sex ratio. The ratio can also be biased already at hatching as it is shown for the mountain plover Charadrius montanus ( [45], but just within 10% of sex ratio difference. Heg et al [43] did not find any sexual difference in survival of chicks during the hatch-to-fledge period in eurasian oystercatshers Haematopus ostralegus.…”
Section: Sex Issues In Chicksmentioning
confidence: 78%
“…Heg et al [43] did not find any sexual difference in survival of chicks during the hatch-to-fledge period in eurasian oystercatshers Haematopus ostralegus. Some higher hatch-to-fledge survival was shown for males of mountain plover chicks: 54.8% vs. 47.2% in females [45]. But Saunders & Cuthbert [46] found significant male-biased survival during pre-fledging in Ch.…”
Section: Sex Issues In Chicksmentioning
confidence: 95%